The united states' threat to saudi arabia over crude oil production cuts in 2022 - Ismiyatun, Ismiyatun; Wulandari, Safira Dwi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
The United States' threat to Saudi Arabia following the 2022 decision by OPEC+ to cut crude oil production by two million barrels per day reveals the complex interplay between domestic political pressures and international energy geopolitics. This study aims to analyze the underlying internal and external factors influencing the U.S. response, using the Internal-External Setting theory developed by Snyder, Bruck, and Sapin. Employing a qualitative policy analysis approach, the research utilizes data from peer-reviewed journals, official government reports, and credible media coverage to examine U.S. foreign policy behavior. The findings show that internal factors—such as public opinion, inflationary pressures, the upcoming midterm elections, and media framing—played a critical role in shaping Washington's confrontational stance. Simultaneously, external dynamics, including Saudi Arabia’s leadership within OPEC+, post-pandemic energy market volatility, and shifting global power relations, further escalated diplomatic tensions. The study reveals how domestic political needs intersect with international strategic interests in driving foreign policy decisions. By applying the Internal-External Setting theory, this research highlights the interdependence of domestic and global considerations in modern energy diplomacy. The implications are significant for understanding U.S. geopolitical behavior in an era of energy insecurity and shifting alliances. This study contributes to the broader discourse on global energy governance, international economic stability, and the evolving nature of U.S.-Middle East relations.